2017
DOI: 10.1039/c6an02048h
|View full text |Cite
|
Sign up to set email alerts
|

Infrared imaging of high density protein arrays

Abstract: We propose in this paper that protein microarrays could be analysed by infrared imaging in place of enzymatic or fluorescence labelling. This label-free method reports simultaneously a large series of data on the spotted sample (protein secondary structure, phosphorylation, glycosylation, presence of impurities, etc.). In the present work, 100 μm protein spots each containing about 100 pg protein were deposited to form high density regular arrays. Using arrays of infrared detectors, high resolution images coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…In the absence of easily available and well-characterized proteins, such calibrations cannot take place and comparison with previous work cannot be achieved. In the field of FTIR spectroscopy only, transmission cells for aqueous solution [42] , microfluidic modulation FTIR [43] , vibrational circular dichroism [44] , ATR with various incidence angles and internal reflection elements of different refractive indices [45] , [46] , microscopy or imaging of 2D arrays of proteins [47] , [48] or human tissue sections [49] , [50] , [51] and new techniques as AFMIR [52] etc. produce spectra that, though similar, display specific features that prevent a single spectral database to be used for all approaches.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of easily available and well-characterized proteins, such calibrations cannot take place and comparison with previous work cannot be achieved. In the field of FTIR spectroscopy only, transmission cells for aqueous solution [42] , microfluidic modulation FTIR [43] , vibrational circular dichroism [44] , ATR with various incidence angles and internal reflection elements of different refractive indices [45] , [46] , microscopy or imaging of 2D arrays of proteins [47] , [48] or human tissue sections [49] , [50] , [51] and new techniques as AFMIR [52] etc. produce spectra that, though similar, display specific features that prevent a single spectral database to be used for all approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the processing time is extremely short, especially in comparison with current LC-MS (liquid chromatography-mass spectrometry) or CE (capillary electrophoresis) procedures. The measurement of a FTIR spectrum takes a maximum of 5 minutes; the analysis in 96 or 384-well plates is already available and the use of microarrays of proteins is under development [25] , drastically increasing samples throughput. In addition, data analysis can be fully automated, dramatically reducing spectral interpretation time.…”
Section: Discussionmentioning
confidence: 99%
“…A previous literature report states that the observed amide II bands in SC at about 1540 and 1508 cm −1 can be attributed to α-helical conformation and β-pleated sheets, respectively (Lin et al., 1996). Recently, a lot of new insights about the protein structure have been proposed by Goormaghtigh’group (Grimard et al., 2004; Sarroukh et al., 2013; Baldassarre et al., 2015; De Meutter et al., 2017), who reported that the tertiary structure of protein also existed and could change in the absence of significant secondary structure modification. The changes could be monitored by kinetics of deuteration or polarized IR light.…”
Section: Resultsmentioning
confidence: 99%